Formation of a future specialist of a new worldview based on a synergistic approach (Pedagogy of Higher and Secondary Education, 2012)
Chebotarova I. V. Formation of a future specialist of a new worldview based on a synergistic approach.The negative influence of the population of the planet on the biosphere, which leads to the global problems of humanity, is characterized in the article on the basis of scientists’ thoughts. It has been proved that synergetics as interdisciplinary teaching, gives a possibility to form in a person a new outlook on the world and yourself. This is a science, which unites specialists from different branches of knowledge for the joint solution of problems on the moral and spiritual basis.
Keywords: biosphere; synergetics; perception of the world; specialist; nonlinear thinking